2016
DOI: 10.1080/15384101.2016.1231280
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic cells form actin-based bridges with adjacent cells to provide intercellular communication during rounding

Abstract: In order to achieve accurate chromosome segregation, eukaryotic cells undergo a dramatic change in morphology to obtain a spherical shape during mitosis. Interphase cells communicate directly with each other by exchanging ions and small molecules via gap junctions, which have important roles in controlling cell growth and differentiation. As cells round up during mitosis, the gap junctional communication between mitotic cells and adjacent interphase cells ceases. Whether mitotic cells use alternative mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
(53 reference statements)
1
14
0
Order By: Relevance
“…4B), the subtle difference was not significant, consistent with recent work showing cGAS generates only low levels of cGAMP upon activation by chromatin [34,53]. Mitotic cells could potentially take up exogenous cGAMP via the SLC19A1 transporter [76,77] or directly from neighboring cells [78,79]. Recent work has revealed a primordial role for cGAMPdependent STING activation in triggering autophagy through WIPI2/ATG5 in a TBK1/IRF3-independent manner [80].…”
Section: Cgas and Sting Are Non-responsive During Mitosissupporting
confidence: 83%
“…4B), the subtle difference was not significant, consistent with recent work showing cGAS generates only low levels of cGAMP upon activation by chromatin [34,53]. Mitotic cells could potentially take up exogenous cGAMP via the SLC19A1 transporter [76,77] or directly from neighboring cells [78,79]. Recent work has revealed a primordial role for cGAMPdependent STING activation in triggering autophagy through WIPI2/ATG5 in a TBK1/IRF3-independent manner [80].…”
Section: Cgas and Sting Are Non-responsive During Mitosissupporting
confidence: 83%
“…Alternatively, Cx43 might undergo recycling from the multivesicular endosomes to the plasma membrane. In accordance with this model, Cx43 has been shown to be transported to early endosomes during the early phases of mitosis and is thought to undergo recycling to the plasma membrane in the late phases (Boassa et al, 2010;Fykerud et al, 2016;Vanderpuye et al, 2016).…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, connexosomes have been suggested to be able to undergo a transformation into a connexin-enriched multivesicular endosome, which is associated with their fusion with early endosomes [79][80][81][82]. Some studies also indicate that following endocytosis, connexins can under certain conditions undergo recycling from endocytic compartments back to the plasma membrane [32, 75,81,[83][84][85]. It has also been suggested that Cx43 can be transported directly from early secretory compartments to lysosomes without prior transport to the plasma membrane [30].…”
Section: Endocytosis and Degradation Of Gap Junctionsmentioning
confidence: 99%
“…SMURF2 also mediates the PKCinduced endocytosis and degradation of Cx43 [79]. In IAR20 cells, but not in HeLa cells, SMURF2 is also required for the remodeling of Cx43 gap junctions during mitosis [84]. However, it is unclear whether SMURF2 regulates gap junction endocytosis directly by catalyzing Cx43 ubiquitination or indirectly via another, yet unknown, protein [79].…”
Section: Smurf2mentioning
confidence: 99%